The future roles of school principals in light of the trend towards a knowledge society - Mansour, Rimah Mudawi (Arab Journal for Sciences and Research Publishing, 2024)
The study targeted the future roles of school principals in light of the orientation towards the knowledge society from the point of view of Najran school principals. The researcher used the survey’s descriptive curriculum, identifying from (22) paragraphs, divided into two dimensions: building a knowledge society, and ICT. It was distributed to a sample of (82) managers and directors, (79.6%) of the (103) study community. The study’s findings found that the future roles of school principals and principals in light of the trend towards a knowledge society in the first dimension: building a knowledge society, averaged (4, 35 out of 5) to a very large extent. The results also showed that school departments’ future roles in the second dimension: ICT, averaging (4.38 out of 5) were extremely high, It also shows that there are no statistically significant differences at the indicative level (α≤0.05) Future roles of school administrators and principals in light of the trend towards the knowledge society from the sample’s perspective, attributable to species variables (Male, Female), and experience, based on the findings, the researcher recommended facilitating executive procedures and regulations in schools, creating innovative and innovative ways to leverage available technological capabilities and utilizing social media sites to spread knowledge inside and outside schools.